A Note on the Effect of Sulphate of Potash on Hydraulic Conductivity, Water Holding Capacity and Crop Yields under Rainfed Agriculture at Anantapur - Reddy, D Subbarami; Reddy, D Ramchandra; Chary, G Venkata Nadha (Annals of Arid Zone, 2016)
.